1992
DOI: 10.1080/09542299.1992.11083185
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium in tea: SEC-ICP-MS speciation studies of infusions and simulated gastrointestinal digests

Abstract: The speciation of aluminium in tea infusions and in vitro gastrointestinal digests of tea infusions has been investigated using size exclusion chromatography coupled to inductively coupled plasma mass spectrometry (SEC-ICP-MS). At pH 2.5, following simulated gastric treatment, AI from tea eluted at a similar retention volume to that obtained for an aqueous AI standard. At pH 5.5, an aqueous AI standard was eluted from an SEC column in Tris buffer (AI recovery "" 1 00%) only in the presence of a complexing agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…If zero bioavailability of Al from tea is assumed, then the bioavailability of Al from food alone is 0.64 percent. However, Al in tea has been shown to be largely bound in high relative molecular mass complexes 28 . In this research only 15 percent of Al in tea was chemically labile, so if it is assumed that only 15 percent of Al in tea is potentially available for uptake, then Al bioavailability from food is 0.53 percent.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…If zero bioavailability of Al from tea is assumed, then the bioavailability of Al from food alone is 0.64 percent. However, Al in tea has been shown to be largely bound in high relative molecular mass complexes 28 . In this research only 15 percent of Al in tea was chemically labile, so if it is assumed that only 15 percent of Al in tea is potentially available for uptake, then Al bioavailability from food is 0.53 percent.…”
Section: Discussionmentioning
confidence: 74%
“…Ruoff 29 found that the bioavailabilities of manganese, nickel, and cadmium in water were similar to their bioavailabilities in food. Furthermore, the bioavailabilities of manganese, zinc, copper, or Fe from food were the same whether the metals were naturally present in the food or were added separately as a tracer 28 …”
Section: Discussionmentioning
confidence: 99%
“…Other speciation methods are based on kinetic discrimination of the species, using fluorometric or spectrometric reagents. [8][9][10] A few studies have been carried out for the speciation of Al in tea infusions. [10][11][12] Al species in tea infusion could be categorized into three groups: large organic compounds, small stable organic compounds and free ionic form of Al.…”
Section: Introductionmentioning
confidence: 99%
“…6 Studies on Al species under stomach conditions before and after gastrointestinal digestion were published. 10 Ultrafiltration studies showed that as much as 86% of the 0.45 µm filterable Al in tea infusions was retained by a 20000 Da molecular-mass cut-off filter and 96% was retained by 10000 and 500 Da molecular-mass cut-off filters. 22 This indicates that the large part of Al in tea infusions exists as large organic complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation